Structural and functional method of stage- by-stage forming of unified regional law enforcement forces taking in account data processing principles - Orlov, М. М. (Honor and Law, 2019)
Structural and functional method of stage-by-stage forming of unified regional law enforcement forces is developed. This method unlike the existing ones, can utilize principles and norms of data processing under complicated conditions. The method is applicable for all control units at any level.